HOW MARKETING DEPARTMENT ENFORCES SUSTAINABILITY: A QUALITATIVE INQUIRY - Efendi; Mulyono, Riandiva Pervinatalie (Journal of Business Studies and Management Review, 2026)
How the marketing department enforces sustainability has become an interesting subject for academic study. The marketing process comprises marketing analysis, planning, implementation, and control. To understand how sustainability is being integrated into the marketing process, we conduct a qualitative inquiry. Interviews with managers and executives of private businesses were conducted to gather the data. Analysis of the data reveals some interesting findings of the subject studied.